Sistema informático de ingreso y control de pacientes en el consultorio de medicina general del departamento médico de la Espam MFL - Alcívar Cevallos, Roberth Abel (2012)
In order to optimize the flow of information in the area of General Medicine of the Medical Department of the Polytechnic School of Manabi Agricultural Felix Manuel Lopez Sock City Region Bolivar, was created and implemented a computer system, for this purpose conducted an evaluation, which determined that the processes carried out within that establishment, requiring faster and more accurate at time of entry / modification of a new patient, to search for information, generate statistical reports, among other activities. In creating the software application is made use of tools and techniques for developing next generation software, such as process flow diagram (PFD), MySqlWorkBench 5.2CE, MySQL 5.5, the paradigm of three layers (data business layer, presentation layer) and the programming language Microsoft Visual Basic 2010. The installation and commissioning of the application, an interview with the clinic doctors allowed to validate the software, obtaining satisfactory results as the registration of the main characteristics of patients, doctors, illness, medical consultations, issue of medical records, statistics of patients seen, among others.